Molecularly Imprinted Nanozymes for Selective Hydrolysis of Aromatic Carbonates Under Mild Conditions - Tien Tan Bui; Yan Zhao (Nanomaterials)
Aliphatic polycarbonate (PC) can be readily hydrolyzed by lipase, but bisphenol A-derived PC (i.e., BPA-PC) lacks enzyme catalysts for their efficient hydrolysis due to the high hydrophobicity and rigidity of its polymer backbone. This study aims to develop an artificial nanozyme for the selective hydrolysis of small-molecule aromatic carbonates as model substrates for BPA-PC. The catalyst is prepared through molecular imprinting of cross-linkable micelles in a one-pot reaction using a thiourea template and a zinc-containing functional monomer. The resulting water-soluble nanoparticle resembles a hydrolytic metalloenzyme to bind the appropriately shaped aromatic carbonate substrate in the active site, with the nearby zinc acting as a cofactor to activate a water molecule for the nucleophilic attack on the carbonate. Catalytic hydrolysis is observed at room temperature and pH 7, with a rate acceleration of 1 × 106 for diphenyl carbonate.